Formal methods, foundations and applications 14th Brazilian Symposium, SBMF 2011, São Paulo, Brazil, September 26-30, 2011, Revised Selected Papers - Brazilian Symposium on Formal Methods 2011 Sâo Paulo, Brazil); Simao, Adenilso; Morgan, Carroll; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 14th Brazilian Symposium on Formal Methods, SBMF 2011, held in Sao Paulo, Brazil, in September 2011; co-located with CBSoft 2011, the second Brazilian Conference on Software: Theory and Practice. The 13 revised full papers were carefully reviewed and selected from 37 submissions. The papers presented cover a broad range of foundational and methodological issues in formal methods for the design and analysis of software and hardware systems as well as applications in various domains.
Electronic reproduction.
Keywords: Formal methods (Computer science) -- Congresses; Electronic books